Analysis of The Role of Affective Commitment As an Intervening Variable in The Relationship Between Effective Reward and Organizational Learning in Advertising Industry - Umi Zunaidah; Wulandari; Suparman; Sitti Usmia; Dedik Wiryawan (Jurnal Informasi dan Teknologi, 2024)
This research aims to analyze the influence of extrinsic reward and intrinsic reward on affective commitment. Primary data, collected through surveys of respondents from the target population, served as the data source. Data collection methods include in-depth interviews, observations, and surveys using questionnaires. The respondents targeted for the survey are employees who have permanent employee status and have worked for at least one year are targeted for the survey. This study employs descriptive research methods. Sampling employed non-probability techniques, such as convenience sampling. The research results revealed a positive and significant impact of both extrinsic and intrinsic rewards on affective commitment. This shows that giving rewards, both in extrinsic and intrinsic form, can increase employee emotional commitment to the company. Apart from that, the results of the analysis also show that affective commitment has a positive and significant effect on knowledge transfer. This emphasizes the importance of having employees with high emotional commitment, because this can increase their ability to share knowledge and information with colleagues. To develop these findings, companies can consider improving reward programs that can increase employee affective commitment, both through extrinsic and intrinsic rewards. Apart from that, companies can also pay attention to other factors that can increase affective commitment, such as a supportive work culture, opportunities for development, and recognition of employee contributions. In this way, companies can create a work environment that supports knowledge transfer and improves overall performance.